How Has the Crisis of 2008-2009 Affected Subjective Well-Being? - Heinz Welsch; Jan Kühling (University of Oldenburg, Department of Economics, 2011)
Results of life satisfaction regressions for more than 91,000 individuals are used to investigate how the macroeconomic crisis of 2008-2009 has affected subjective well-being (SWB) in 30 OECD countries. In a number of countries, the effect of the crisis on a representative person's SWB is of a similar magnitude as the effects of the most important personal life events. Our findings highlight the importance of GDP fluctuations for SWB.
Keywords: E32; I31; E61; 330; macroeconomic crisis; growth; stability; subjective well-being